THE PROTECTION POLICY OF THE HYDROLOGICAL UNITY OF PEAT LANDS IN RIAU PROVINCE, INDONESIA - Febri Yuliani; Zulkarnaini Zulkarnaini; Saktioto Saktioto; Abdul Sadad (Universitas Syiah Kuala, 2022)
This article examines the policies aimed at protecting peat ecosystems in Indonesia and identifies gaps or challenges in controlling forest and land fires (karhutla), particularly concerning the preservation of the Hydrological Unity Policy in Riau Province, Indonesia. The peat ecosystem is a cohesive entity that encompasses various elements, influencing each other to maintain balance, stability, and productivity. The Hydrological Unity of Peat (KHG) refers to the peat ecosystem situated between rivers, between rivers and seas, and/or within swamps. The Peat Ecosystem serves multiple functions, including safeguarding water availability, conserving biodiversity, storing carbon as oxygen producers, and contributing to climate regulation. These functions are categorized into protected and cultivation functions. However, rapid development has exerted significant pressure on preserving the KHG. This study emphasizes the need for comprehensive support from all sectors of society and active community participation to effectively reduce the risk of forest and land fires.